Evaluation of the Correlation of (He Distance Between the Alveolar Crest and Cementoenamel Junction Inpreiapical. Bitewing and Panoramic Radiographs with its Actual Distance - J. Yazdani; F. Kaviarri; MT. Chiisazi (Tehran University of Medical Sciences, 2005)
Statement of Problem: In spite of the limitations of Radiography, diagnosing of periodontal diseases without having accurate radiographs is inadequate because it provides a visible image of the supporting bone to the clinician and works as a fixed measure of the supporting bone during the study.Purpose: The aim of this study is to compare the precision of preiapical, bitewings and panoramicradiographs in determining the distance between the alveolar crest (AC) and cementoenamel junction (CEJ) of teeth. Materials and Methods: Statistically this is a survey study in which 120 interproximal surfaces of teeth were measured during surgery by periodontal probing and recorded as the actual measurement. Then 40 sites underwent bitewing, 40 sites preapical and 40 others panoramic radiography and the distance of CEJ up to the alveolar crest of bone was measured on them by periodontal probe and recorded. Then each group was analyzed separately and the Pearson's correlation coefficient was examined for the data.Results: The results of this study showed that when the thickness of the remaining bone in a millimeter limit is important for (he surgeon, the bitewing radiography has a prime importance, but when bone loss ismoderate, the panoramic radiography showing %89 of the cases close to the actual measure, can be acceptable. On the other hand, in anterior sites for determining the bone alteration, preiapical radiography with a 0.93 correlation coefficient is superior to the panoramic radiography with a correlation coefficient of 0.72 and we suggest it for examining the changes of bone in these sites. Conclusion: whenever the bone alteration is moderate or severe, it seems that, bitewing radiography is of particular importance, but when the bone loss is little, panoramic radiography can be used and there is no needto put the patient on unnecessary radiation.